LIQUIDITY RATIO ANALYSIS FOR FINANCIAL PERFORMANCE ASSESSMENT (CASE STUDY: UPK LANGGENG MAKMUR, PRINGAPUS DISTRICT, SEMARANG REGENCY) - Widowati, Lis; Kurniawati , Andi (Universitas Islam Lamongan, 2024)
This research aims to analyze liquidity ratios with the aim of being used as an assessment tool to financial performance at UPK Langgeng Makmur. This research uses a descriptive qualitative approach method. The data studied is in the form of UPK Langgeng Makmur's financial reports from 2019 to 2021. The standard used is the liquidity ratio standard according to Kasmir. From the results of calculating the average liquidity ratio, the financial performance condition of UPK Langgeng Makmur is said to be good. From the calculation of the current ratio from 2019 to 2021, it can be said to be good, although everything is still below the standard current ratio, namely 200%, but it is still said to be good because it is not less than 150%. Meanwhile, according to quick ratio calculations in 2019 and 2020 it was declared